The Reduced Form of a Block Recursive Model - Hans Schneeweiss; Erich Otto Maschke; M. Pfannes (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
Various estimators of the reduced form of a block recursive model are investigated and compared to each other. In particular it is shown that the structural reduced form estimator, which results from estimating separately each block of the block recursive model by some efficient method and then solving the system for the endogenous variables, is more efficient than the OLS estimator of the reduced form. Other reduced form estimators derived from OLS or Two Stage LS estimators of a partially reduced form have intermediate efficiency properties. The paper has been published in Schneeweiss et al (2001), but without the appendices.
urn:nbn:de:bvb:19-epub-1689-4
Keywords: 519; Block recursive model; reduced form; simultaneous equations model; Simultanes Gleichungssystem; Schätztheorie; Theorie